Effects of organic carbon, inorganic phosphorus, and phosphorus-solubilizing bacteria on maize growth, nutrient uptake, and rhizosphere phosphorus availability - Zhou, Guangwei; Wang, Mingshuang; Zhu, Hongxia; Wang, Jing; Zhang, Shaomin (Frontiers in Plant Science, 2025)
IntroductionPhosphate-solubilizing bacteria (PSB), phosphorus(P), and carbon(C )influence the activity of microbes, P availability in soil, and the growth of crops.MethodsIn this study, pot experiments were conducted to evaluate the effects of C, P and PSB on maize growth, nutrient uptake, and P availability in the rhizosphere soil. Based on a 2×3×2 complete factorial design, the pot experiment was performed at two P levels (0 and 50 mg kg-1 potassium dihydrogen phosphate), three C levels (0, 60, and 120 mg kg−1 glucose) and two PSB levels (0 and 60 mL pot-1).ResultsThe results showed that PSB addition caused an average increase of 3.03% in the biomass of maize shoots compared to control group with no PSB. C addition resulted in a significant decrease in the biomass of maize shoots, N concentration, and the uptake of nitrogen and P by maize plants. In the absence of exogenous P, PSB addition led to a decrease in N concentration, P concentration, N uptake, and P uptake in maize plants. On the other hand, at exogenous P concentration of 50 mg kg−1, PSB addition enhanced N concentration, N uptake, and P uptake in maize plants. The addition of C and PSB led to average decreases of 13.36% and 8.05% in the Olsen P content, respectively, while water-soluble P decreased by 25.52% and 28.42%, respectively. In contrast, microbial biomass C content showed average increases of 78.15% and 60.39%, respectively, while microbial biomass P content increased by 67.52% and 16.19%, respectively.DiscussionThe results showed that C and PSB addition increased the immobilization of microbial C, P and the reduced forms of labile P susceptible to leaching. On the other hand, PSB and exogenous P promoted plant growth by increasing nutrient uptake. The findings of this study will be helpful in promoting the rational use of P fertilizers, reducing P leaching and increasing crop yield.